Fuel processing innovation (Badriah) based on Refuse Derived Fuel (RDF) at Pangkep Environmental Office - Ali, Nur Annisa; Ibrahim, Muh. Akmal; Yunus, Muhammad (Institute Of computer Science (IOCS), 2024)
Innovation in environmental management is an important effort to enhance the efficiency and effectiveness of governance, particularly in addressing increasingly complex waste management issues. The Environmental Agency of Pangkep Regency has implemented a waste-to-fuel processing innovation (Badriah) based on Refuse Derived Fuel (RDF) through the Badriah Plant, aimed at reducing waste accumulation in landfills (TPA) while simultaneously producing environmentally friendly alternative fuel. This study employs a descriptive qualitative approach to analyze the implementation of the RDF innovation and evaluate aspects such as relative advantage, compatibility, complexity, trialability, and observability. The results show that the RDF innovation has significant advantages in reducing dependence on fossil fuels, although it still faces challenges regarding community acceptance and technology optimization. This innovation reflects the local government's commitment to sustainable waste management and supports renewable energy production while also generating economic value. However, to ensure the sustainability of this innovation in the future, improvements in environmental impact mitigation and community involvement are necessary.